2022
DOI: 10.1039/d1cc06981k
|View full text |Cite
|
Sign up to set email alerts
|

SNS ligand-assisted catalyst activation in Zn-catalysed carbonyl hydroboration

Abstract: Zinc amido and thiolate SNS complexes exhibit distinct ligand-assisted pre-catalyst activation pathways for carbonyl hydroboration using pinacolborane.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 29 publications
1
25
0
Order By: Relevance
“…The stoichiometric reaction of 1 with HBpin afforded an insoluble black precipitate and N-borylated L 1 , as confirmed by EI-MS (Figure S15). In the previous work with a Zn­(SNS) 2 hydroboration precatalyst, we also showed that the basic amido group binds strongly to the Bpin group, reducing the ligand’s ability to coordinate the metal . As a result, we turned to the less basic pyrrolyl group in L 2 . , …”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…The stoichiometric reaction of 1 with HBpin afforded an insoluble black precipitate and N-borylated L 1 , as confirmed by EI-MS (Figure S15). In the previous work with a Zn­(SNS) 2 hydroboration precatalyst, we also showed that the basic amido group binds strongly to the Bpin group, reducing the ligand’s ability to coordinate the metal . As a result, we turned to the less basic pyrrolyl group in L 2 . , …”
Section: Resultsmentioning
confidence: 92%
“…In the previous work with a Zn(SNS) 2 hydroboration precatalyst, we also showed that the basic amido group binds strongly to the Bpin group, reducing the ligand's ability to coordinate the metal. 42 As a result, we turned to the less basic pyrrolyl group in L 2 . 47,51−53 Treatment of HL 2 with 1 equiv of NiBr 2 (DME) afforded Ni II Br(κ 3 -NNN) (2) as a brown solid (Scheme 3).…”
Section: Synthesis Of Ni II (Ph) (κ 3 -Nnn) (7)mentioning
confidence: 99%
See 1 more Smart Citation
“…15 Given the literature precedence for imine hydroboration 33 in addition to a previous report of the activity of a ligand backbone for H 2 activation, 34 the observed hydroboration of the imine backbone in the S Me NS ligand is not unexpected. Additionally, the hydroborated ligand was previously isolated and characterized in our lab, 35 and its presence in this reaction mixture was conrmed by comparison of 1 H and 11 B NMR data. It is of note that this intermediate is preferentially formed over Mn-H derived from traditional bifunctional B-H activation by 41.2 kcal mol −1 (Fig.…”
Section: Catalytic Cycle For Nitrile Dihydroborationmentioning
confidence: 99%
“…3 Zinc, as an abundant and economically accessible first row metal, is one of the most environmentally friendly and biocompatible elements that can be employed in synthetic and catalytic processes. 4 Indeed, various hydroboration reactions of N-heterocycles, 5 carbonyls, 6 isocyanates, 7 carbon dioxide 8 and alkynes 9 have been catalysed using zinc-based systems. Reports to date of zinc complex-catalysed dihydroboration of nitriles both involve dimeric precatalysts (A, 10 B 11 ) with strongly donating ligands (Scheme 1).…”
mentioning
confidence: 99%